Intersection of Studious Legal Research Philosophies and Scientific Chics In Nigeria: A Comprehensive Analysis - Emedolu, Cyriacus O; Okuma, Nwachukwu Camillus; Chukwudi , Remi; Odigbo, Jude; Ojiakor, Chinyere Theodora; Okeke, Mathew Arinze (Journal of Ecohumanism, 2024)
This study investigates the Intersection of Studious Legal Research Philosophies and Scientific Chics in Nigeria: a comprehensive analysis considering the challenges and opportunities in transitioning from traditional legal research approaches to systematic, procedural, and scientific methodologies in academic legal research in Nigeria. The study employed Non-doctrinal legal research design, though OSCOLA and NALT citation style were employed do to the nature of the study. Likert scale was used to compute the Mean for descriptive analysis and ANOVA was used for inferential statistical analysis, four hypotheses were tested to examine the utilization of scientific approaches, availability of relevant data and tools, institutional support, and the impact of citation styles on scientific legal research. The findings reveal that the utilization of scientific approaches remains low, despite adequate availability of resources. Institutional support for scientific methodologies is insufficient, and the current citation styles significantly affect the implementation of scientific approaches. Recommendations include comprehensive training programs, enhanced access to research tools, prioritization of scientific methodologies by academic institutions, and revision of citation styles or to develop Okuma-NC (hybrid) citation model to better support scientific research. These insights aim to contribute to the advancement of legal scholarship in Nigeria by promoting more rigorous, empirical, and interdisciplinary research practices.